Identification of two flavin monooxygenases from an effluent treatment plant sludge metagenomic library - Singh, Ajit; Chauhan, Nar Singh; Thulasiram, H. V.; Taneja, Vibha; Sharma, Rakesh (Bioresource Technology, 2010)
Oxygenases are useful for the production of many industrially important molecules. Screening of an effluent treatment plant (ETP) sludge metagenomic library identified two clones encoding proteins, B1 and B2, with similarity to putative Flavin monooxygenases from Mesorhizobium loti and Sphingomonas wittichi, respectively. The deduced amino acid sequences show only 20% identity, but both have a paired Rossman fold and a flavin monooxygenase (FMO) motif. B1 and B2 appear to be members of the Flavin-containing monooxygenase and the Baeyer-Villiger monooxygenases subfamilies, respectively. When expressed in Escherichia coli, the two clones produced activities that oxidized indole to a mixture of indigo and indirubin pigments. These results suggest that B1 and B2 have potential as a biocatalyst in indigo/indirubin production. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Indigo; Indirubin; Metagenome; Metagenomic; Monooxygenase

Genome sequence of rheinheimera sp strain A13L, isolated from pangong lake, india - Gupta, Hemant Kumar; Gupta, Rinkoo Devi; Singh, Ajit; Chauhan, Nar Singh; Sharma, Rakesh (Journal of Bacteriology, 2011)
Rheinheimera sp. strain A13L, which has antimicrobial activity, was isolated from alkaline brackish water of the high-altitude Pangong Lake of Ladakh, India. Here we report the draft genome sequence of Rhienheimera sp. strain A13L (4,523,491 bp with a G + C content of 46.23%). The genome is predicted to contain genes for marinocine and colicin V production, which may be responsible for the antimicrobial activity of the strain.